An Evaluation of an Apple Canopy Density Mapping System for a Variable-rate Sprayer. Issue 30 (2019) - Hu, Mengying; Whitty, Mark
Abstract: This paper proposes methods for evaluating an apple canopy density mapping system as an input for a variable-rate sprayer for both trellis-structured (2D) and standalone (3D) apple orchards. The mobile terrestrial system used in this paper consists of a 2D LiDAR (Light Detection and Ranging), three RGB-D cameras and a GPS-RTK module. A 3D point cloud was generated for 2D or 3D tree row, then converted to a 2D matrix with density distribution information for the variable-rate sprayer. Quad frames were placed in the trees to gain ground truth data for GPS validation and canopy density. They were extracted from the 3D point cloud by intensity thresholding and RANSAC along with their locations and timestamps. Five evaluation methods are discussed in this paper to validate the robustness and repeatability of the canopy density mapping system: Quad locations will be used to evaluate GPS accuracy; Quad density deviation and overall deviation in multiple passes will evaluate the repeatability. Then manual classified quad density will be compared with automatic density extraction to evaluate correlation; The misalignment of the point cloud from both sides of a tree row exists but this paper compares between two sides of the same row. The result indicates that it might be sufficient to scan from one side only to halve the field work. The proposed system will help the decision making in a variable-rate sprayer. The evaluation methods are practical, easy to be applied in similar approaches to map canopy density.